Multi-access Edge Computing Smart Relocation Approach from an NFV Perspective - Bernad, Cristina; Kjorveziroski, Vojdan; Roig, Pedro Juan; Alcaraz, Salvador; Gilly, Katja; Filiposka, Sonja (Springer Nature, 2023)
This paper analyses the virtualised entities migration process implementation within the ETSI-compliant edge framework, considering the necessary multi-access edge computing (MEC) modules information interchange required for instantiation, termination and migration of MEC applications. Based on the variant of the MEC-NFV architecture and the functions of each element of it, a communication process that includes network function virtualisation (NFV) interfaces is provided, as a step towards the unresolved challenge of modelling and developing a migration procedure that is aligned with the MEC standardisation process.
Keywords: Edge Computing; Optimisation; Standardisation; Process Design; Mobile Nodes